The Dundee whaling fleet : ships, masters and men - Archibald, Malcolm (Dundee University Press, 2013)
At the end of the 19th century, Dundee was Europe's premier Arctic whaling port. From humble beginnings in the 1750's this national industry had survived French and American wars, privateers, economic slumps, storms, heart-wrenching disasters and some amazing triumphs.From 1860 until the 1880's, Dundee built the most efficient Arctic vessels in the world. Despite being only a small city on the east coast of Scotland, as the 19th century closed, it was the most important Arctic whaling port in Europe.The Dundee Whaling Fleet gives an overview of Dundee's experience in Arctic whaling, including a valuable guide to every ship in the fleet with statistics, dates and a thumbnail history. It also gives sketches of the most prominent of the whaling masters, Dundee shipping companies and 350 of the tens of thousands of seamen who took the ships north.